Potensi Pemanfaatan Ekstrak Kubis Ungu (Brassica oleracea L.) sebagai Indikator Asam Basa Alami - Erwin -; Muhammad Asfian Nur; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2015)
The study of potential use of extracts and fractions of purple cabbage (Brassica oleracea L.) as an indicator of acid-base has been conducted. This research aims to determine the color change at a certain pH to extract total, n-hexane, ethyl acetate and methanol fraction. Based on the results of the test changes color only total extracts and methanol fraction that is suitable as indicator. Statistical test that the t test for total titration end point extracts, t calculate is smaller than t table [0.4241 <2.776], it showed no significant difference between the endpoint using the total extract with bromine thymol blue indicator. While the endpoint for methanol fraction having t calculategreater than t table [6.323> 2.776],indicating the end point of the titration using methanol fraction was significantly different compared with bromine thymol blue indicator.Keywords: Brassica oleracea L, indicator, and acid-base